2020
DOI: 10.1042/bsr20200219
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical staining reveals differential expression of ACSL3 and ACSL4 in hepatocellular carcinoma and hepatic gastrointestinal metastases

Abstract: Long-chain fatty acyl CoA synthetases (ACSLs) activate fatty acids by CoA addition thus facilitating their intracellular metabolism. Dysregulated ACSL expression features in several cancers and can affect processes such as ferroptosis, fatty acid β-oxidation, prostaglandin biosynthesis, steroidogenesis and phospholipid acyl chain remodelling. Here we investigate long chain acyl-CoA synthetase 3 (ACSL3) and long chain acyl-CoA synthetase 4 (ACSL4) expression in liver malignancies. The expression and subcellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 84 publications
(111 reference statements)
0
47
0
Order By: Relevance
“…Interestingly, ACSL4 and ALOX5 were found to be significantly up-regulated in HCC patients with high CIFI values, even though they facilitate the execution of ferroptosis ( Liu et al, 2015 ; Yuan et al, 2016 ; Doll et al, 2017 ). However, it is worth noting that both ACSL4 and ALOX5 are over-expressed in HCC as compared to normal livers, and promote the progression of the disease ( Xu et al, 2011 ; Chen et al, 2020 ; Ndiaye et al, 2020 ; Wang et al, 2020 ). Thus, the over-expression of ACSL4 and ALOX5 contributes to the proliferation and progression of HCC, but renders the patients more susceptible to ferroptosis inducers.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, ACSL4 and ALOX5 were found to be significantly up-regulated in HCC patients with high CIFI values, even though they facilitate the execution of ferroptosis ( Liu et al, 2015 ; Yuan et al, 2016 ; Doll et al, 2017 ). However, it is worth noting that both ACSL4 and ALOX5 are over-expressed in HCC as compared to normal livers, and promote the progression of the disease ( Xu et al, 2011 ; Chen et al, 2020 ; Ndiaye et al, 2020 ; Wang et al, 2020 ). Thus, the over-expression of ACSL4 and ALOX5 contributes to the proliferation and progression of HCC, but renders the patients more susceptible to ferroptosis inducers.…”
Section: Discussionmentioning
confidence: 99%
“… 31 , 32 Studies have shown that ferroptosis participates in tumor immunoregulation. 9 , 33 Ferroptosis plays a vital role in anti-tumor immunotherapy. However, there are few studies on the association between HSPB1 and immunocytes in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Other validated proteins, though not enriched in the two pathways mentioned above, also play a role in the process of liver and gastrointestinal diseases. CPT1A and ACSL3, which are responsible for fatty acid oxidation, have been proved to stimulate gastric cancer and hepatocellular carcinoma cell growth and migration [ 34 36 ]. MCAM (CD146) involves in actin cytoskeleton rearrangement, blood vessel endothelial cells remodeling and intercellular junction [ 37 ].…”
Section: Discussionmentioning
confidence: 99%